Odpowiedzi

2010-03-24T20:17:45+01:00
A) (2x - y + 4) - (z + 14y) + ½ z = 2x - y + 4 - z - 14y + ½ z = 2x - 15y - 0,5z
b) (-2 + ⅘ y - 2z) + (2z - 0,2y + 2x) = -2+ ⅘ y - 2z + 2z - 0,2y + 2x = 2x - 3/5y -2
c) 4z - 2e - (12a + 3z - 1,5e) = 4z - 2e -12a -3z + 1,5e = -12a - 0,5e -z
d) 12y - (3x - 8y) + (2x - 4y) + x = 12y -3x + 8y + 2x -4y + x = 16y


mam nadzieje, że dobrze : )
6 3 6
2010-03-24T20:17:54+01:00
B) (-2 + 4/5y - 2z) + (2z-0,2y + 2x) = -2 + 4/5y - 2z + 2z - 0,2y + 2x = -2 + 3/5y +2x


c) 4z - 2e - (12a +3z - 1,5e) = 4z - 2e - 12a - 3z + 1,5e = z + 0,5e - 12a


d) 12y - (3x - 8y) + (2x - 4y) +x = 12y - 3x + 8y + 2x - 4y +x = 16y
3 4 3